The eternity of the spiritual heritage of Abay (Journal of Philosophy Culture and Political Science, 2020)
The article reveals the enduring value of the spiritual heritage of Abay and clarifies the value at thepresent time. Abay’s teaching, regardless of nationality, religion, races, is a worldwide spiritual teaching.Abay’s wisdom lies in his cognition of the world from a cognitive point of view. I would like to note thatthe works of Abay Kunanbayev vividly reflect the worldview, way of life, way of life, rituals and traditionsof the Kazakh people.Emphasizing the value of the works and relying on the teachings of Abay, ways of overcoming thecauses and consequences of the spiritual decline of humanity are proposed. Having shown the life philosophyof the Kazakh people through the worldview of Abay, the authors pay attention to the issuesof the formation and education of an “integral personality” and emphasize the value of this idea in themodern period.The humanistic idea of Abay is comprehensively considered as the core of the life philosophy of theKazakh people, the positive existential nature of Abay’s worldview, the problem of promoting Abay’sheritage, the role of Abay’s pragmatism in modern spiritual revival, the modern application of the categoriesof truthfulness and justice of Abay, the significance of Abay’s doctrine of honor and consciencein the modern world, the idea of a “good person”, views on education and science, Abay’s religiousworldview.The article considers the Abai’s Heart as a center of deep meaning that connects the mind andconscience. The heart is recognized as the main form of conscious actions, such as thinking, reasoning,knowledge, and cognition. Connecting the world with the heart, which is created by rational vision,demonstrates the idea that the heart is the abode of humanity and virtue. The question of maintainingthe heart in perfect purity is raised by considering the words of Edification of Abay.Key words: Abay, philosophy,” whole person”, kindness, personality, humanity, heart, mind.